SARS-CoV-2 Genomic Surveillance Enables the Identification of Delta/Omicron Co-Infections in Argentina - Pisano, María Belén; Sicilia, Paola; Zeballos, Maximiliano; Lucca, Andrea; Fernandez, Franco; Castro, Gonzalo M.; Goya, Stephanie; Viegas, Mariana; López, Laura; Barbás, María Gabriela; Ré, Viviana E. (Frontiers in Virology, 2022)
Molecular surveillance of SARS-CoV-2 is crucial for early detection of new variants and lineages. In addition, detection of coinfections with more than one SARS-CoV-2 lineage have been sporadically reported. In this work, surveillance of SARS-CoV-2 variants was performed on 2067 RNA samples (Ct>30) obtained during December 2021 and January 2022 from Córdoba province, Argentina, by real time RT-PCR specific for variants of concern (VOC) and variants of interest (VOI) relevant mutations (TaqMan™ SARS-CoV-2 Mutation Panel, Applied Biosystems). The following distribution of variants was obtained: Omicron (54.9%), Delta (44.2%) and Lambda (0.8%). Three samples (0.1%), obtained the last week of December, were compatible with a Delta/Omicron co-infection. One of them was sequenced by NGS-Illumina, obtaining reads for both VOCs. One of the co-infected patients presented with severe symptoms, was not vaccinated and presented risk factors (older than 60 years, arterial hypertension). We describe for the first time in Argentina, the identification of cases of co-infection with two SARS-CoV-2 lineages, VOCs Delta and Omicron, during the third COVID-19 wave in the country (a high viral circulation period), when Delta and Omicron co-circulated. Our findings highlight the importance of continuing molecular surveillance, in order to elucidate possible recombination events and the emergence of new variants.